Zn0.52V2O5−a⋅1.8 H2O Cathode Stabilized by In Situ Phase Transformation for Aqueous Zinc‐Ion Batteries with Ultra‐Long Cyclability. Issue 35 (7th July 2022) - Liang, Wenhao; Rao, Dewei; Chen, Tao; Tang, Rongfeng; Li, Jun; Jin, Huile
Abstract: Developing cathode materials integrating good rate performance and sufficient cycle life is the key to commercialization of aqueous zinc‐ion batteries. The hyperstable Zn0.52 V2 O5− a ⋅1.8 H2 O (ZVOH) cathode with excellent rate performance has been successfully developed via an in situ self‐transformation from zinc‐rich Zn3 V3 O8 (ZVO) in this study. Different from the common synthetic method of additional Zn 2+ pre‐insertion, ZVOH is obtained from the insertion of structural H2 O and the removal of excess Zn 2+ in ZVO, ensuring the lattice structure of ZVOH remains relatively intact during the phase transition and rendering good structural stabilities. The ZVOH delivers a reversible capacity of 286.2 mAh g −1 at 0.2 A g −1 and of 161.5 mAh g −1 at 20 A g −1 over 18 000 cycles with a retention of 95.4 %, demonstrating excellent rate performance and cyclic stability. We also provide new insights on the structural self‐optimization of Zn x (CF3 SO3 ) y (OH)2 x − y ⋅ n H2 O byproducts and the effect on the mobility of Zn 2+ by theoretical calculations and experimental evidence. Abstract : A hyper‐stable cathode Zn0.52 V2 O5− a ⋅1.8 H2 O (ZVOH) for aqueous zinc‐ion batteries was prepared by in situ self‐transformation using Zn3 V3 O8, a Zn‐rich vanadate as precursor. ZVOH has excellent structural stability and still maintains a capacity of 95.4 % after 18 000 cycles at the ultrahigh current density of 20 A g −1 .